Assessment of the Political Risk in a Country: a Practitioner’s View - Arrieta Padilla, Carlos (Revue générale de droit, 1989)
Political risk is inherent to foreign investment. It stems from either the government's or the political regime's instability, or restrictive and compelling governmental policies. To cope with this risk, two complementary instruments are used: risk assessment and deterrent measures.Taking into consideration South America, the author explains how the political risk assessment is realized through risks indexes, public or corporate: each carries its own criteria as shown here by the analysis of General Motors and Union Carbide methods of assessment.The author then discusses the means available to the investor to forecast and minimize the negative effects of the actualization of a political risk. He identifies two main categories of deterrent measures: business oriented strategies carried out by the investor or legal techniques of protection. Among the latter, the author analyses the stabilization and internationalization clauses; the security offered by certain bilateral or multilateral treaties to foreign investment; the guarantees agreed upon by organizations such as the Multilateral Investment Guarantee Agency; the transfer of domicile of legal entities.